Brain Abscess Due to Wolinella recta and Streptococcus intermedius - Thomas J Marrie; Elizabeth Kerr (Canadian Journal of Infectious Diseases)
The authors present a case of a 62-year-old female with a frontal lobe brain abscess caused by Wolinella recta and two strains of Streptococcus intermedius. One of the strains of S intermedius was resistant to penicillin. Resolution of the abscess required 60 days of antibiotic therapy and aspiration on four occasions. The source of the brain abscess could not be determined. This is the first case in which W recta has been isolated from a brain abscess.